THE HISTORY OF THE RELATIONS OF AFRICAN COUNTRIES WITH THE UZBEKISTAN SSR - Bobokulov Okhunjon Akhmatovich (Journal of Learning on History and Social Sciences, 2024)
This article discusses the policy of developed countries in the process of Congo's independence and Uzbekistan's diplomatic relations with the SSR, following the feelings of friendship and brotherhood towards the Congolese people and helping them with food products